PENGARUH KECEPATAN ANGIN, KELEMBABAN DAN SUHU UDARA TERHADAP KONSENTRASI GAS PENCEMAR SULFUR DIOKSIDA (SO2) DALAM UDARA AMBIEN DI SEKITAR PT. INTI GENERAL YAJA STEEL SEMARANG - Dea Budi Istantinova (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
In the process of melting steel industry specifically that using fuels MFO (Marine Fuel Oil) may cause air pollution, which is air contamination by the gases from the combustion (furnace metals) such as SO2. Pollutants pollutants released from the stack of PT. General Steel core Yaja Semarang to The air would cause pollution and causing the changes the concentration of SO2 in ambient air in the surrounding areas. The concentration of gas pollutant in the air other than influenced by the the amount of sources of pollution, meteorological parameters also influence the the concentration of gas pollutant in the air so that the environmental conditions can not be ignored. Wind speed, air temperature and humidity are part of the meteorological parameters that can influence the the concentration of gas pollutant in the air.